2019
DOI: 10.3847/1538-4357/ab1a37
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Massive Star Activities in the Final Years through Properties of Supernovae and Their Progenitors

Abstract: Recent observations of supernovae (SNe) just after the explosion suggest that a good fraction of SNe have the confined circumstellar material (CSM) in the vicinity, and the pre-SN enhanced mass loss may be a common property. The physical mechanism of this phenomenon is still unclarified, and the energy deposition into the envelope has been proposed as a possible cause of the confined CSM. In this work, we have calculated the response of the envelope to various types of sustained energy deposition starting from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 70 publications
0
36
0
Order By: Relevance
“…A similar study to ours has been recently performed by Ouchi & Maeda (2019), where the authors investigated the influence of the late stage energy deposition into the RSG envelopes on their SN light curves. They found that a super-Eddington energy deposition changes the structure of the RSG envelope so much that the resulting 'light curves and the evolution of photospheric velocity are all inconsistent with the observations of SNe II'.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…A similar study to ours has been recently performed by Ouchi & Maeda (2019), where the authors investigated the influence of the late stage energy deposition into the RSG envelopes on their SN light curves. They found that a super-Eddington energy deposition changes the structure of the RSG envelope so much that the resulting 'light curves and the evolution of photospheric velocity are all inconsistent with the observations of SNe II'.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…This type of very confined CSM potentially contributes to early peaks in some Type II-P SN light curves (Moriya et al 2011;Morozova et al 2017;Das & Ray 2017;Moriya et al 2018;Morozova et al 2020). The CSM structure depends on the details of the heating history, as slow and steady heating will inflate the star without producing CSM and will not match observations of Type II-P SNe (Ouchi & Maeda 2019). However, our models typically exhibit sharp spikes in the wave-heating rate at the onset of nuclear burning phases.…”
Section: Implications For Supernovae and Their Progenitorsmentioning
confidence: 93%
“…To explain the origin of the CSM, a number of mechanisms can trigger greatly enhanced mass loss prior to the final stellar explosion, including common-envelope-triggered mass loss (Chevalier 2012;Schrøder et al 2020), pulsation-induced mass loss in pulsational pair-instability SNe (PPISNe; Umeda & Nomoto 2003;Woosley 2017;Marchant et al 2019;Leung et al 2020a;Woosley 2019;Renzo et al 2020a), enhanced stellar wind in super-asymptotic giant branch stars (Jones et al 2013;Moriya et al 2014;Nomoto & Leung 2017;Tolstov et al 2019), and wave-driven mass loss (Quataert & Shiode 2012;Shiode & Quataert 2014;Fuller 2017;Fuller & Ro 2018;Ouchi & Maeda 2019;Leung & Fuller 2020;Kuriyama & Shigeyama 2021).…”
Section: Circumstellar Medium Interaction Mechanismmentioning
confidence: 99%